The trade-off between inflation and economic activity in Brazil - Alexis Maka; Fernando de Holanda Barbosa (Institute for Applied Economic Research (ipea), 2017)
This paper contrasts empirically four leading models of inflation dynamics - the accelerationist Phillips curve (APC), the new Keynesian Phillips curve (NKPC), the hybrid Phillips curve (HPC), and the sticky information Phillips curve (SIPC). We employ an encompassing Phillips curve specification that allows us to derive tests for these models within a single framework. According to the generalized method of moments (GMM) estimator, the evidence suggests that the restrictions implied by the NKPC, HPC and SIPC are rejected for the period after the Real Plan in Brazil. Only the restrictions implied by the APC are not rejected. However, when we construct confidence regions that are robust to weak instruments, it is not possible to reject any of the Phillips curve specifications, including the NKPC.
Keywords: E12; E31; E32; 330; Phillips curves; weak instruments; fully robust confidence regions